Uji Aktivitas Antioksidan Ekstrak Etanol 96% Daun Tigaron (Crateva religiosa G.Forst.) Asal Kalimantan Selatan Menggunakan Metode DPPH - Sari, Rika Amara Widya; Saputri, Revita; Khairunnisa, Khairunnisa (Universitas Borneo Lestari, 2024)
Ethanol extract leaves of Crateva religiosa G.Forst. has antioxidant activity using the FRAF method of 357.9 ± 17.6 μmol/L., but the antioxidant activity of the 96% ethanol extract of C. religiosa G.Forst leaves. from South Kalimantan has not been reported. This study aims to determine the secondary metabolites and antioxidant activity of the 96% ethanol extract of Tigaron (C. religiosa G.Forst.) leaves from South Kalimantan using the DPPH method measured with a UV-Vis spectrophotometer. Tigaron (C. religiosa G.Forst.) leaves 96% ethanol extract was prepared by maceration method. Tigaron (C. religiosa G.Forst.) leaves antioxidant activity test was carried out at concentrations of 50 ppm, 75 ppm, 100 ppm, 125 ppm and 150 ppm using quercetin as a comparison. Phenol, flavonoid, quinone, and tannin were all detected in the phytochemical screening. Testing the antioxidant activity of the quercetin comparator showed an IC50 of 3.0151 (very strong) and the 96% ethanol extract of tigaron (C. religiosa G.Forst.) leaves showed an IC50 of 94.9082 ppm (strong). Based on the results obtained that the 96% ethanol extract of tigaron (C. religiosa G.Forst.) leaves from South Kalimantan has antioxidant activity in the strong category.